2012
DOI: 10.1111/j.1445-2197.2012.06093.x
|View full text |Cite
|
Sign up to set email alerts
|

Intercostal catheter insertion: are we really doing well?

Abstract: This study identified a large number of preventable errors for ICC insertion in trauma patients. Standardized institutional credentialing systems may be required to ensure adequate proficiency of trainees performing this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…ATLS ® training has standardised the teaching of ICD insertion and the technique described is regarded currently as the gold standard in terms of safety. 6 Despite the widespread adoption of ATLS ® training and principles as part of both undergraduate and postgraduate training worldwide, there continues to be a steady stream of literature reporting an unacceptably high rate of complications [1][2][3] and even mortality 5 associated with the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATLS ® training has standardised the teaching of ICD insertion and the technique described is regarded currently as the gold standard in terms of safety. 6 Despite the widespread adoption of ATLS ® training and principles as part of both undergraduate and postgraduate training worldwide, there continues to be a steady stream of literature reporting an unacceptably high rate of complications [1][2][3] and even mortality 5 associated with the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…However, the procedure is associated with a complication rate that may be as high as 30%. [1][2][3] Numerous case reports have documented individual cases of fatal complications such as ventricular perforation 4 and pulmonary artery injury following ICD insertion. 5 In light of this, the correct safe technique of insertion is one of the core skill sets that is heavily emphasised in the Advanced Trauma Life Support ® (ATLS ® ) course.…”
mentioning
confidence: 99%
“…The results of the present study showed that registrars and consultants working in our regional ED were unable to reliably place a marker over the 4th or 5th ICS. Inability of ED doctors to correctly identify the 4th or 5th ICS might lead to increased patient morbidity, particularly if placed inferior to the diaphragm . The present study has demonstrated a preponderance to identify a site for potential ICC insertion inferior to Bulau's position, approaching the point at which the diaphragm is in direct contact with the costal portion of the parietal pleura in expiration .…”
Section: Discussionmentioning
confidence: 59%
“…The correct technique of insertion has been extensively taught in ATLS 1 , yet despite these educational efforts, the complication rate from TT insertion can be as high as 30% [6][7][8][9][10]. The majority of complications are usually related to malpositioning of the drain [6][7][8][9][10]. The desire to ascertain correct positioning of the tube to document radiological improvement of the pathology, and to exclude potential complications, are all important factors influencing the request for a postinsertion CXR [2,3].…”
Section: Discussionmentioning
confidence: 99%